Physical Activity and Mental Health Among Veteran Lung and Colorectal Cancer Survivors: Results from the Behavioral Risk Factor Surveillance System. (3rd April 2019) - McDaniel, Justin; Albright, David L.; Patrick, Sarah L.; Beck, Alan; Piontek, Amy; Kono, Shintaro; Thomas, Kate H.; Fletcher, Kari L.; Anton, Philip M.
Abstract: The mental health status of veteran cancer survivors is understudied. Given that studies show that physical activity (PA) may alleviate mental distress in cancer patients, the purpose of this study was to examine the relationship between PA and mental distress in veteran lung and colorectal cancer survivors. Data for the present study were retrieved from the 2016 Behavioral Risk Factor Surveillance System. The relationship between PA and the number of mentally distressful days in the last 30 days was examined among veteran lung cancer survivors and veteran colorectal cancer survivors with survey-weighted multiple linear regression. After adjusting for relevant covariates, results showed that colorectal cancer survivors had significantly more mentally distressful days compared to lung cancer survivors, B = 0.75 (95% confidence interval [CI] = 0.64, 0.86). Furthermore, PA was significantly related to fewer days of mental distress in both lung and colorectal cancer survivors, B = −0.33 (95% CI = −0.43, −0.23); however, the relationship was stronger among colorectal cancer survivors, B = −1.15 (95% CI = −1.60, −0.69). Introducing PA in the plan of care among veterans diagnosed with cancer may alleviate mental distress.